Robust adaptive feedforward output-feedback tracking control for microalgae cultures. Issue 1 (July 2017) - Schaum, A.; Weisbarth, H.; Meurer, T.
Abstract: A feedforward-feedback control strategy for trajectory tracking of microalgae cultures is developed and experimentally evaluated. On the basis of the Droop model an inversion-based feedforward control is determined, which steers the biomass from given initial to final values in a finite prescribed time. Feedback control is employed for disturbance resilience and improving the stability properties of the desired trajectory. The approach is tested using numerical simulations and experiments in a lab-scale photocatalytic reactor with Chlorella sorokiniana .